(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the work of the parity commission, established by the resolution of the Central Executive Committee of the USSR dated January 29, 1926, on the basis of relevant archival materials. The author notes that after the approval of the border between the RSFSR, the TSR and the UZSSR by Resolution No. 62 of the Presidium of the All-Russian Central Executive Committee dated May 5, 1925, disputes broke out between the Union republics and the governments of autonomous republics and regions on many points of this border. By a resolution of the Central Executive Committee of the USSR dated January 29, 1926, a parity commission was established to settle these disputes, which was chaired by D.I. Petrovsky. In total, the parity commission considered more than 45 issues. The technical commission established under the parity commission included persons di- rectly involved in the transfer of many lands of the Kyrgyz Autonomous Region to the Uzbek SSR in 1924-1925. Specific examples show that the parity commission did not work constructively. In total, the Kyrgyz side presented its claims on 24 sites, of which only 6 were resolved in favor of the Kyrgyz. For the remaining 18 sites, the commission made a decision against the interests of Kyrgyzstan. At the same time, the Uzbek SSR filed claims on 7 sites, of which 5 were resolved in favor of the Uzbek SSR. Due to unfair decisions made by the parity commission, the results of the commission’s work were considered only in the autumn of 1926. Already on April 25, 1926, the Central Executive Committee of the Kyrgyz Autonomous Region was one of the first to object to the decisions of the Parity Commission.